2016
DOI: 10.1089/aid.2015.0170
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Free Treatment of Hepatitis C Virus in HIV/Hepatitis C Virus-Coinfected Subjects Results in Increased Serum Low-Density Lipoprotein Concentration

Abstract: Chronic hepatitis C virus (HCV) infection is associated with lower serum concentration of low-density lipoprotein (LDL-C), the primary cholesterol metabolite targeted pharmaceutically to modulate cardiovascular risk. Chronic infection with human immunodeficiency virus (HIV) and treatment with antiretrovirals (ARVs) are associated with dyslipidemia and increased risk of cardiovascular disease. In subjects coinfected with HIV and HCV, lipid abnormalities associated with either infection alone are often attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…A study reported significantly lower levels of TC and higher levels of TG in coinfection compared with healthy controls, while another study reported significantly lower levels of large LDL but higher levels of large HDL particles and small HDL particles . Of note, many other studies as illustrated in Table ,B reported either lower or higher levels of lipids in coinfection compared with HIV monoinfection or HCV monoinfection or healthy controls, but the differences between the groups were either not statistically significant or the P values were not reported …”
Section: Resultsmentioning
confidence: 95%
“…A study reported significantly lower levels of TC and higher levels of TG in coinfection compared with healthy controls, while another study reported significantly lower levels of large LDL but higher levels of large HDL particles and small HDL particles . Of note, many other studies as illustrated in Table ,B reported either lower or higher levels of lipids in coinfection compared with HIV monoinfection or HCV monoinfection or healthy controls, but the differences between the groups were either not statistically significant or the P values were not reported …”
Section: Resultsmentioning
confidence: 95%
“…This might explain a direct effect of HCV clearance on lipid metabolism. Townsend et al [13] reported a rapid increase in LDLc and TC values that was also sustained after treating HIV/HCV-coinfected patients with ledipasvir and sofosbuvir (LDV/SOF) combination therapy for 12 weeks. Thus, the increment in serum LDLc and TC levels occurs in both HIV/HCV-coinfected and HCV mono-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…HCV modulates host lipid metabolism as part of its natural lifecycle from virion entry, polyprotein processing and replication, to assembly and release . LDL‐C in HCV mono‐infected or HCV/HIV co‐infected patients treated with sofosbuvir plus ribavirin or sofosbuvir/ledipasvir therapy was correlated with a viral decline in serum titer, suggesting a direct influence of HCV clearance on serum cholesterol . However, the association between treatment and changes in lipid metabolism is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] LDL-C in HCV monoinfected or HCV/HIV co-infected patients treated with sofosbuvir plus ribavirin or sofosbuvir/ledipasvir therapy was correlated with a viral decline in serum titer, suggesting a direct influence of HCV clearance on serum cholesterol. [16][17][18] However, the association between treatment and changes in lipid metabolism is unclear.…”
Section: Introductionmentioning
confidence: 99%